Early Outcomes and Perioperative Complications of the Arthroscopic Latarjet Procedure: Systematic Review and Meta-analysis. Issue 9 (July 2019) - Cerciello, Simone; Corona, Katia; Morris, Brent Joseph; Santagada, Domenico Alessandro; Maccauro, Giulio
Background: The arthroscopic Latarjet-Bristow procedure is emerging as a reliable alternative to the open procedure. The reduced soft tissue damage with potential advantages of early pain control and functional recovery is attractive. However, the operation is technically more demanding, and there are concerns regarding the potential for increased recurrence and complication rates. Purpose: To evaluate the available literature focusing on the reported functional outcomes and complications of the arthroscopic Latarjet procedure and compare them with the open procedure. Study Design: Systematic review and meta-analysis. Methods: A comprehensive systematic review was performed with the keywords "arthroscopy, " "arthroscopic, " "Latarjet, " and "Bristow, " with no limit regarding the year of publication. The review was limited to the English-language articles, and each article was evaluated with a modified MINORS (methodological index for nonrandomized studies) scoring system. Results: Fourteen studies met the inclusion criteria and were included in the review. Overall, 813 patients met inclusion criteria, with a mean follow-up of 24.5 months. The mean Walch-Duplay and Rowe scores were 89.6 and 90.2, respectively. The overall complication rate was 16.5%; intraoperative conversion to open surgery, 2%; recurrence, 2.5%; and revision surgery, 5.6%. When only comparative studies were considered, the overall complication rates were 23.7% (arthroscopically) and 15.3% (open). The recurrence and revision surgery rates were 6.5% and 5.7% in the study group, while the corresponding values in the control group were 4% and 2.9%. The mean MINORS score was 14.5 (11.6 for noncomparative studies and 19 for comparative studies). Conclusion: The arthroscopic Latarjet-Bristow procedure is reliable. Outcomes are satisfactory, with less pain and faster recovery in the first postoperative week. However, the procedure is technically demanding, and higher rates of complications and reoperations should be expected. Finally, the arthroscopic operation is much more expensive in terms of implanted materials than the open procedure.